RELIGIOUS PRACTICE PERFORMED BY THE HINDUS AT SENDURO VILLAGE, LUMAJANG, EAST JAVA - Harsana, I Ketut Gede; Parimartha, I Gde Parimartha; Ardika, I Wayan Ardika; Suastika, I Made Suastika (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2015)
The religious practice performed by the Hindus at Senduro Village cannot be separated from the context of the relationship between the dominant culture of the Bali Hindus and the subculture of the Hindus at Senduro Village. The Bali Hindus who are stronger culturally, economically and symbolically affect the religious practice performed by the Hindus at Senduro Village in regard to their tatwa (philosophy), acara (ritual) and organization. The problems formulated in this article are as follows: the forms, the contributing factors, and the meaning of the religious practice performed by the Hindus at Senduro Village. The qualitative method was used to obtain the data needed in the present study. The theories used are the theory of practice, the theory of subaltern, the theory of semiotics, and the theory of identity. Before the temple was constructed the Hindus at Senduro Village was classified as the followers of what is referred to as Kejawen. The reason was that their religious practice was highly specific and different from the religious practices performed by the Hindus in the other areas. After the Mandara Giri Semeru Agung Temple was constructed, the Hindus at Senduro Village were affected by the Balinese in the way in which they perform their religious practice. Such an impact could be observed from the aspect of their tattwa (philosophy), the aspect of their religious ritual, and the aspect of their religious organization.